2019
DOI: 10.1007/s12571-019-00959-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of market production on rural household food consumption: evidence from Uganda

Abstract: Food access is an important element of food security that has since long been a major concern of rural households. One intervention to improve food access has been increased promotion of market production in the hope that households will get increased income and access to food through the market rather than through self-sufficiency characteristic of subsistence production. We examine the effect of market production on household food consumption using a case of rice in western Uganda, where rice is largely a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 46 publications
2
27
2
Order By: Relevance
“…As illustrated above, both groups of smallholders consume the same types of food groups-severely lacking in some critical nutrients. The lack of contribution by the business to household nutrition diversity is in contrast to some studies that have found that an improvement in farm income has a positive effect on a household's dietary diversity [63,65,126,127]. Nevertheless, the findings are consistent with the fact that the business participants, who happen to have relatively higher incomes, spend similar amounts on food as non-participants.…”
Section: Contribution To Food and Nutrition Securitycontrasting
confidence: 49%
“…As illustrated above, both groups of smallholders consume the same types of food groups-severely lacking in some critical nutrients. The lack of contribution by the business to household nutrition diversity is in contrast to some studies that have found that an improvement in farm income has a positive effect on a household's dietary diversity [63,65,126,127]. Nevertheless, the findings are consistent with the fact that the business participants, who happen to have relatively higher incomes, spend similar amounts on food as non-participants.…”
Section: Contribution To Food and Nutrition Securitycontrasting
confidence: 49%
“…Increased market production can result in higher HDDS but also in less calorie intake (Ntakyo & van den Berg, 2019). Furthermore, Sekabira and Nalunga (2020) showed that increased HH production for own consumption increased HDDS more than increased production for trade.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, commercialized production of food crops as cash crops, such as rice in Uganda (Ntakyo & van den Berg, 2019), sugarcane in Mexico (Dewey, 1981), and vegetables in Guatemala (Immink & Alarcon, 1993), has been found to be undesirably associated with dietary deterioration and lower food caloric intake.…”
Section: Discussionmentioning
confidence: 99%
“…SeeDeWalt (1993), von Braun andKennedy (1995) and WorldBank (2007) for survey of early literature. Recently, while some recent studies reported positive effects of cash cropping and commercialization on food security and nutritional outcomes(Kuma, Dereje, Hirvonen, & Minten, 2018;Kuma et al, 2015;Ogutu, Gödecke, & Qaim, 2019),Anderman et al (2014) andNtakyo and van den Berg (2019) found that cash cropping hurts food security among cocoa producers in Ghana and calorie intake among commercialized rice producers in Uganda respectively.…”
mentioning
confidence: 99%